Agrobacterium‐mediated transformation of reed (Phragmites communis Trinius) using mature seed‐derived calli. Issue 1 (20th August 2012) - Kim, Yong‐Goo; Sharmin, Shamima Akhtar; Alam, Iftekhar; Kim, Kyung‐Hee; Kwon, Suk‐Yoon; Sohn, Jung‐Hoon; Kim, Sun‐Hyung; Liu, Gongshe; Lee, Byung‐Hyun
Abstract Reed (Phragmites communis) is a potential bioenergy plant. We report on its first Agrobacterium‐mediated transformation using mature seed‐derived calli. The Agrobacterium strains LBA4404, EHA105, and GV3101, each harboring the binary vector pIG121Hm, were used to optimize T‐DNA delivery into the reed genome. Bacterial strain, cocultivation period and acetosyringone concentration significantly influenced the T‐DNA transfer. About 48% transient expression and 3.5% stable transformation were achieved when calli were infected with strain EHA105 for 10 min under 800 mbar negative pressure and cocultivated for 3 days in 200 μm acetosyringone containing medium. Putative transformants were selected in 25 mg l−1 hygromycin B. PCR, and Southern blot analysis confirmed the presence of the transgenes and their stable integration. Independent transgenic lines contained one to three copies of the transgene. Transgene expression was validated by RT‐PCR and GUS staining of stems and leaves.